DAMPAK NAPI ASIMILASI TERHADAP NAIKNYA ANGKA KRIMINALITAS NASIONAL DI MASA PANDEMI - Diana Novianti (Program Studi Magister Ilmu Hukum Universitas Kader Bangsa, 2020)
At first was when the government released pp no. 21 years 2020 about large scale social restrictions ( psbb ) to accelerate the handling of covid-19. So implicates to weak economic community , and increasing pressure life of the need for helplessness them before the plague this global pandemic. In order to cut chain for the transmission of covid-19, the directorate general of correctional institution until early may have spent 39.273 inmates and children through the provision of assimilation and integration. There are 93 people ( 0.23 percent ) is among those who issued in the un back berulah and caught for a criminal offense again. This concern writer through writing this time to make the incident as a criminal highlight the unusual. With the approach of juridical, normative writer mengelaborasi tried to us about a factor all that make prisoner at assimilation is back in the criminal deeds, pandemic and how to tackle the phenomenon of the indonesian police crime